2022
DOI: 10.3389/fnut.2022.889042
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response and Substitution Analyzes of Sweet Beverage Consumption and Body Weight in Dutch Adults: The Lifelines Cohort Study

Abstract: Background/MethodsProspective studies investigating sweet beverages and body weight associations show inconsistent results. Within the SWEET project, we examined prospective dose-response associations of sugar-sweetened beverages (SSB), low/no-calorie beverages (LNCB), and fruit juice with body weight-related outcomes among 78,286 Dutch adults followed for ~4 years. Baseline intakes were assessed using a validated food-frequency questionnaire (FFQ) with 150 ml representing a standard serving. Outcome variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Cohort studies that did not adjust for total energy intake showed a positive association for juice with body weight (0.21 kg; 95% CI, 0.15-0.27 kg), whereas studies that adjusted for energy intake found an inverse association (−0.08 kg; 95% CI, −0.11 to −0.05; P for meta-regression <.001). Significant differences were also found for study location with studies conducted in North America (0.14 kg; 95% CI, 0.02-0.26) showing significant body weight gain, whereas no significant association was observed among studies conducted in Europe (−0.15 kg; 95% CI, −0.37 to 0.08; P for meta-regression = .04). There were no significant subgroup differences found for RCTs in adults (eFigures 16 and 17 in Supplement 1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Cohort studies that did not adjust for total energy intake showed a positive association for juice with body weight (0.21 kg; 95% CI, 0.15-0.27 kg), whereas studies that adjusted for energy intake found an inverse association (−0.08 kg; 95% CI, −0.11 to −0.05; P for meta-regression <.001). Significant differences were also found for study location with studies conducted in North America (0.14 kg; 95% CI, 0.02-0.26) showing significant body weight gain, whereas no significant association was observed among studies conducted in Europe (−0.15 kg; 95% CI, −0.37 to 0.08; P for meta-regression = .04). There were no significant subgroup differences found for RCTs in adults (eFigures 16 and 17 in Supplement 1).…”
Section: Resultsmentioning
confidence: 95%
“…No RCTs were identified among children. A total of 25 studies were identified for adults (268 095 adults), with 6 prospective cohort studies with 8 comparisons, and 19 RCTs . The screening and exclusion flowchart is presented in eFigure 1 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Differences across categories of SSB and LNCB consumption were assessed using ANOVA or Kruskal–Wallis for continuous variables and Chi-square tests for categorical variables. Previous restricted cubic spline analyses with data of the Lifelines cohort did not show strong evidence for non-linear associations between SSB or LNCB consumption and body weight and waist circumference changes [ 12 ], and further exploration in other cohorts did not produce further evidence (data not shown). Thus, multiple linear regression analyses were conducted to assess associations between baseline daily SSB and LNCB consumption, and yearly body weight and waist circumference changes in each cohorts.…”
Section: Methodsmentioning
confidence: 93%
“…Only a few prospective studies have examined the theoretical replacement of SSBs with LNCBs, and its association with weight measures [ 9 11 ], showing either beneficial [ 9 ] or no associations [ 10 , 11 ]. In contrast, we recently observed that the theoretical replacement of SSB consumption with LNCB consumption was associated with higher weight and waist circumference change amongst 78,826 Dutch adults [ 12 ]. Thus, despite the low caloric content of LNCBs and its suggested beneficial effects on weight gain based on RCTs, data from prospective studies do not unambiguously support the hypothesis that LNCBs may prevent weight gain.…”
Section: Introductionmentioning
confidence: 98%
“…The incidence of overweight/obesity was increased by 8% (95%CI: 6%-11%) and the incidence of abdominal obesity was increased by 5% (95%CI: 2%-7%). Substitution analysis found that beverage intake was negatively associated with body weight (−0.05kg year −1) and waist circumference (−0.08cm year −1), and the incidence of overweight/obesity was reduced by 9% (95%CI: 3 to 14%), while replacing sugar-sweetened beverages with an equivalent amount of sugar-replaceable beverages associated with a 6 percent increase in the incidence of overweight/obesity (95%CI: 2 to 10%) [9]. Hence, it is imperative to avoid excessive consumption of both sugar, which plays a crucial role in human metabolism, and non-nutritional sweeteners.…”
Section: Effects Of Sugar Substitutes On Obesitymentioning
confidence: 99%